(untitled) (The Pakistan Development Review, 2025)
Public sector employment remains an attraction for two important reasons: job security and a guaranteed pension (Dixit, 2002). Unlike other countries, Pakistan has not reformed its public sector pension system and has maintained a pay-as-u–go defined benefits type pension system which has resulted in build up of unfunded liability for the government. Pakistan practices a legacy pension system where pensioners are paid directly from the revenues as part of the current expenditures. This practice is inherently unsustainable as pension expenditure growing at around 25 percent, cannot be provided from an economy growing at a significantly lower rate. The pension burden is therefore bound to grow, doubling every four-years. In the fiscal year 2018-19, federal superannuation and pension expenditures were almost 78 percent of the value for PSDP expenditures and it increased in FY 2019-20 to 87 percent (463,419 million Rupees and 533,220 million Rupees respectively). The share of pensions as a percentage of current expenditures is also increasing overtime (for FY 2019-20 it stood around 7.6 percent). 1